STUDIES IN NACL CRYSTAL SURFACES DURING THEIR EVAPORATION IN AIR AND THEIR CHEMICAL DISSOLUTION - YACAMAN, MJ; TORRES, G (UNAM, Instit de Fisic, centro de Inves Materiales, 1977)
Using the method of gold decoration, steps produced in (100) NaCl crystal surfaces are observed. The steps were developed on crystals during evaporation in an impure medium (air) and during chemical dissolution with Moran's reagent. Evaporation in air was
THE AUK
Keywords: STUDIES, NACL, CRYSTAL SURFACES, DURING, EVAPORATION, AIR, CHEMICAL DISSOLUTION; FISICA; FISICA MOLECULAR; ESTRUCTURA MOLECULAR